Analisis Faktor-faktor yang Mempengaruhi Persepsi Wakif dalam Berwakaf melalui Platform Wakaf Hasanah - Fazriah, Siti; Sukmadilaga, Citra; Yuliafitri, Indri (Universitas Proklamasi 45, 2023)
The Hasanah Waqf Crowdfunding Platform was created to make it easier for people to have waqf. With the large potential of waqf in Indonesia, the accumulated amount of waqf in Hasanah Waqf is still far from the target. The research objective was to analyze the factors that influence the perception of waqf through the Hasanah Waqf platform using a combination theory of the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) as well as literacy and trust as external factors. The population is all Muslim communities in Indonesia. The sampling technique used non-probability sampling of as many as 369 people. Quantitative research methods with data analysis techniques Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that perceived ease of use has a positive effect on perceived usefulness. Perceived usefulness and perceived ease of use have a positive effect on people's attitudes. However, the attitude towards the Hasanah Waqf platform has a negative effect on the intention to do waqf through the Hasanah Waqf platform. Subjective norms have a positive effect on intention waqf money through the Hasanah Waqf platform. Perceived behavioral control has a negative effect on the intention of waqf through the Hasanah Waqf platform. Literacy and trust have a positive effect on the intention for waqf through the Hasanah Waqf platform. And the intention has a positive effect on the behavior of waqf money through the Hasanah Waqf platform. This research is expected to provide information to increase the collection of cash waqf in Indonesia.